2004
DOI: 10.1007/s00405-004-0832-y
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycosis of the middle turbinate: an unusual cause of nasal obstruction

Abstract: Actinomycosis is a rare chronic infectious disease caused by Actinomyces israelii, which is an anaerobic filamentous, gram-positive saprophyte organism of the oral cavity. Historically, these bacteria were known as fungi because of their light microscopic appearance. Actinomycosis consists of three different forms: cervico-facial (the most common form), abdominal and pulmonothoracic. It commonly involves the head and neck region including the mandible, paranasal sinuses, lacrimal gland, parotid gland and orbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 9 publications
1
58
0
2
Order By: Relevance
“…Another report described an ulcer-type actinomycotic lesion with A. odontolyticus on the oral mucosa of a patient with diabetes (69). Other locations for actinomycotic lesions categorized as cervicofacial actinomycosis include, for instance, the nasal and sinus region (70)(71)(72); pharynx (73,74); larynx/tonsillae (75-78); middle ear, mastoid, and/or temporal bone (79)(80)(81); and skull base with the craniovertebral junction (82). A somewhat more distant location is the esophagus, from where actinomycotic lesions have also been recovered in both immunocompetent and immunocompromised individuals (83,84).…”
Section: Orocervicofacial Actinomycosismentioning
confidence: 99%
“…Another report described an ulcer-type actinomycotic lesion with A. odontolyticus on the oral mucosa of a patient with diabetes (69). Other locations for actinomycotic lesions categorized as cervicofacial actinomycosis include, for instance, the nasal and sinus region (70)(71)(72); pharynx (73,74); larynx/tonsillae (75-78); middle ear, mastoid, and/or temporal bone (79)(80)(81); and skull base with the craniovertebral junction (82). A somewhat more distant location is the esophagus, from where actinomycotic lesions have also been recovered in both immunocompetent and immunocompromised individuals (83,84).…”
Section: Orocervicofacial Actinomycosismentioning
confidence: 99%
“…Dental cerrahide mukoza hasarlanması paranazal sinüslerde aktinomikoz için zemin hazırlar (6) . Çok az olguda paranazal sinüs aktinomikozu rapor edilmiştir (7,8) . Klasik aktinomiçes enfeksiyonlarından farklı olarak maksillayı içine alan olgular generalize olmayıp lokalize yerleşimlidir.…”
Section: Discussionunclassified
“…[1] Özcan et al reported actinomycosis after the pathologic examination of the surgical excision biopsy material obtained from an intranasal mass which did not respond to the treatment with amoxicillin-clavulanate for 20 days and they have emphasized the importance of actinomycosis in the differential diagnosis of nasal obstruction and nasal cavity mass. [5] In intranasal actinomycosis, endoscopic sinus surgery is recommended for the excision of the lesion and the debridement of surrounding tissue. [5] In our case, sufficient excision could be performed by endoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…[5] In intranasal actinomycosis, endoscopic sinus surgery is recommended for the excision of the lesion and the debridement of surrounding tissue. [5] In our case, sufficient excision could be performed by endoscopic approach. In the treatment of actinomycosis, antibiotic therapy is recommended for 4-6 weeks with or without surgical debridement.…”
Section: Discussionmentioning
confidence: 99%